The role of coping strategies in posttraumatic growth in medical rescue workers - Nina Ogińska-Bulik (Nofer Institute of Occupational Medicine, 2014)
Background: The purpose of the research was to investigate the role of coping strategies with stress in posttraumatic growth in a group of medical rescue workers. Material and Methods: The data on 80 medical rescuers who had experienced traumatic event in their worksite were analyzed. The age of the participants ranged from 21 to 67 years (M = 35.47; SD = 10.21). The Posttraumatic Growth Inventory and Inventory to Measure Coping Strategies with Stress - Mini-Cope were used in the study. Results: The results revealed that the strategy "turning to religion" plays the major role in posttraumatic growth. Conclusions: In the process of emerging positive changes posttraumatic growth avoidance strategies seem to play more important role than strategies focused on the problem itself. Med Pr 2014;65(2):209-217